2012
DOI: 10.1371/journal.pone.0029979
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Human Immune Cell Subsets Identifies miRNA-mRNA Regulatory Relationships Correlated with Cell Type Specific Expression

Abstract: Blood consists of different cell populations with distinct functions and correspondingly, distinct gene expression profiles. In this study, global miRNA expression profiling was performed across a panel of nine human immune cell subsets (neutrophils, eosinophils, monocytes, B cells, NK cells, CD4 T cells, CD8 T cells, mDCs and pDCs) to identify cell-type specific miRNAs. mRNA expression profiling was performed on the same samples to determine if miRNAs specific to certain cell types down-regulated expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
163
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(174 citation statements)
references
References 37 publications
7
163
0
Order By: Relevance
“…Here we demonstrate that, at baseline, O 3 responders have lower expression of three miRNAs, namely miR-143, miR-145, and miR-199a*. Interestingly, miR-143 is known to play a role in neutrophil influx (6) and hence may contribute to the constitutively primed airway of responders. These data suggest that interindividual differences in inflammatory responsiveness to O 3 may be regulated at the miRNA level.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Here we demonstrate that, at baseline, O 3 responders have lower expression of three miRNAs, namely miR-143, miR-145, and miR-199a*. Interestingly, miR-143 is known to play a role in neutrophil influx (6) and hence may contribute to the constitutively primed airway of responders. These data suggest that interindividual differences in inflammatory responsiveness to O 3 may be regulated at the miRNA level.…”
Section: Discussionmentioning
confidence: 65%
“…Thus in this study it was important to identify cell-specific miRNAs that could act as potential confounders since some miRNAs are preferentially expressed in certain cell types (6) and O 3 exposure caused a significant increase in neutrophils in most of our subjects. A comparison of the 10 O 3 -responsive miRNAs to a database of immune cell-specific miRNAs (6) showed that miR-143 and miR-223 are immune cell specific and overabundant in neutrophils and myeloid cells. Interestingly, miR-143 expression changes were significantly correlated with % change in PMN counts, suggesting that miR-143 may serve as a biomarker for increases in PMN cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monticelli et al were the first to investigate the systematic miRNA gene profiling in hematopoietic cells, demonstrating that its profiling was different from non-hematopoietic cells (15). As an important hematopoietic cell-specific miRNA, miR-150 is mainly expressed in B-cells, T-cells and natural killer cells, and plays a critical role in the differentiation of numerous hematopoietic cell lineages, particularly in lymphocyte development and function (14,16). In addition, a recent study has identified that serum circulating miR-150 is a sensor of general lymphocyte activation and may serve as a biomarker of human lymphocyte activation in healthy and disease conditions (17).…”
Section: Role Of Microrna-150 In Solid Tumors (Review)mentioning
confidence: 99%